1993
DOI: 10.1002/j.1460-2075.1993.tb05954.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel small nucleolar RNA (U16) is encoded inside a ribosomal protein intron and originates by processing of the pre-mRNA.

Abstract: We report that the third intron of the Li ribosomal protein gene of Xenopus laevis encodes a previously uncharacterized small nucleolar RNA that we called U16. This snRNA is not independently transcribed; instead it originates by processing of the pre-mRNA in which it is contained. Its sequence, localization and biosynthesis are phylogenetically conserved: in the corresponding intron of the human Li ribosomal protein gene a highly homologous region is found which can be released from the pre-mRNA by a mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
104
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 29 publications
(38 reference statements)
4
104
0
Order By: Relevance
“…This peculiar mechanism has been demonstrated to be involved also in the production of the other snoRNAs recently found to be encoded in introns, U14, U15 U16 and HeLa U17 RNAs (7)(8)(9)41). In the case of U16 RNA, encoded in an intron of the Xenopus gene for r-protein L1, it has been shown that its production is alternative to that of the mature Li mRNA (8). As for U17XS8, we have shown that also the microinjection of a short intronic transcript bearing the U17Xs8 sequence leads to the production of the mature product.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This peculiar mechanism has been demonstrated to be involved also in the production of the other snoRNAs recently found to be encoded in introns, U14, U15 U16 and HeLa U17 RNAs (7)(8)(9)41). In the case of U16 RNA, encoded in an intron of the Xenopus gene for r-protein L1, it has been shown that its production is alternative to that of the mature Li mRNA (8). As for U17XS8, we have shown that also the microinjection of a short intronic transcript bearing the U17Xs8 sequence leads to the production of the mature product.…”
Section: Discussionmentioning
confidence: 94%
“…We show here that the sequences repeated in the introns of S8a gene, on the contrary, code for a small nucleolar RNA (snoRNA), which we named Ul7Xs8 RNA, presumably involved in ribosome production. Similar genome organizations, with snoRNAs encoded in the introns of other genes, are being found with increasing frequency: U14 RNA (6), U15 RNA (7), U16 RNA (8), U17 RNA (9) and U20 RNA (Caizergues-Ferrer, personal communication). We have adopted the name 'U 17' for the Xenopus S8a intron encoded snoRNA after consideration of the strong homology with the U17 RNA described in HeLa cells (9), also called El RNA by Ruff et al (10); however, because of some relevant differences in structure and properties, we identify the Xenopus RNA with a specifying superscript.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A common feature of mammalian snoRNA host gene transcripts is a 5Ј terminal oligopyrimidine sequence, whose precise function with respect to snoRNA synthesis is unknown (14,15). In most cases, it appears that snoRNAs are released from excised, debranched introns by exonucleolytic trimming (16)(17)(18); a minor pathway involves endonucleolytic cleavage of flanking intron sequences (19,20). Many yeast snoRNAs are transcribed as monocistronic or polycistronic precursors from independent transcription units, and proteins involved in their processing have been characterized (21)(22)(23).…”
mentioning
confidence: 99%
“…Particularly, a growing family of snoRNAs contain long, phylogenetically conserved sequence complementarities to rRNAs, which must reflect the biological importance of their transient pairing with pre-rRNA in the nucleolus [4]. Moreover, most of the newly identified snoRNAs exhibit a unique biosynthetic pathway [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Not only they are encoded in introns of protein-coding genes, but they result from a novel form of intronic RNA processing of their host-gene transcript.…”
Section: Introductionmentioning
confidence: 99%